Impact of chronic smoking on traumatic brain microvascular injury: An in vitro study. Issue 15 (23rd June 2021) - Sivandzade, Farzane; Alqahtani, Faleh; Cucullo, Luca
Abstract: Traumatic brain injury (TBI) is a major reason of cerebrovascular and neurological damage. Premorbid conditions such as tobacco smoking (TS) can worsen post‐TBI injuries by promoting vascular endothelial impairments. Indeed, TS‐induced oxidative stress (OS) and inflammation can hamper the blood‐brain barrier (BBB) endothelium. This study evaluated the subsequence of chronic TS exposure on BBB endothelial cells in an established in vitro model of traumatic cell injury. Experiments were conducted on confluent TS‐exposed mouse brain microvascular endothelial cells (mBMEC‐P5) following scratch injury. The expression of BBB integrity–associated tight junction (TJ) proteins was assessed by immunofluorescence imaging (IF), Western blotting (WB) and quantitative RT‐PCR. We evaluated reactive oxygen species (ROS) generation, the nuclear factor 2–related (Nrf2) with its downstream effectors and several inflammatory markers. Thrombomodulin expression was used to assess the endothelial haemostatic response to injury and TS exposure. Our results show that TS significantly decreased Nrf2, thrombomodulin and TJ expression in the BBB endothelium injury models while increased OS and inflammation compared to parallel TS‐free cultures. These data suggest that chronic TS exposure exacerbates traumatic endothelial injury and abrogates the protective antioxidative cell responses. The downstream effect was a more significant decline of BBB endothelial viability, which could aggravate subsequent neurological impairments.